Luxury Brand Perception, Social Influence, and Brand Personality to Predict Purchase Intention - Keni Keni; Ai Ping Teoh; Vincent Vincent; Wulan Purnama Sari (Jurnal Komunikasi, 2022)
The key purpose of this study is to investigate the relationships between luxury brand perception, social influence, and brand personality towards purchase intention. It has been increasingly important for every company to improve its customers’ purchase intention in order to maintain the existence of the company, especially in an increasingly competitive business environment. Hence, this study was conducted to examine whether luxury brand perception, social influence, and brand personality have a positive and significant impact on purchase intention. This study was descriptive research and was conducted by using the cross-sectional method. The population of this research was all Indonesian smartphone users, and the sampling frame was limited to smartphone users who live in Jakarta, whereas purposive sampling was conducted for the data collection from respondents. The data collection was conducted by distributing questionnaires to 100 respondents through the internet and this study used SmartPLS software version 3.2.7. for the data analysis. The result of this study showed that luxury brand perception, social influence and brand personality have a significant and positive impact towards purchase intention. Therefore, it is essential for smartphone companies to maintain their image as a luxury brand, observe and improve customers’ influence to the others about the brand, and also associate the brand’s personalities with customers in order to increase the customers’ purchase intention. Niat pembelian memiliki peran yang semakin penting untuk setiap perusahaan karena pada saat ini, menghasilkan penjualan bukan hanya bertujuan untuk memperoleh keuntungan, tetapi juga untuk mempertahankan keberadaan perusahaan, khususnya dari kondisi persaingan yang semakin meningkat. Tujuan utama penelitian ini adalah untuk meneliti hubungan yang terjadi diantara persepsi terhadap luxury brand, pengaruh sosial dan brand personality terhadap niat pembelian. Penelitian ini merupakan penelitian deskriptif dan dilakukan dengan menggunakan metode cross-sectional. Populasi pada penelitian ini adalah seluruh pengguna smartphone di Indonesia dan sample pada penelitian ini dibatasi pada pengguna smartphone yang berdomisili di Jakarta, dimana purposive sampling digunakan untuk mengumpulkan data dari responden. Pengumpulan data dilakukan dengan mendistribusikan kuesioner kepada 100 oorang responden melalui internet dan penelitian ini menggunakan perangkat lunak SmartPLS versi 3.2.7. untuk melakukan analisis data. Hasil penelitian ini menunjukkan bahwa persepsi terhadap luxury brand, pengaruh sosial dan brand personality memiliki pengaruh yang positif dan signifikan terhadap niat pembelian. Oleh sebab itu, merupakan sebuah hal yang penting bagi perusahaan smartphone untuk mengembangkan persepsi terhadap luxury brand, pengaruh sosial dan brand personality pelanggan untuk meningkatkan niat pembelian pelanggan.